Microbial Community and Abundance of Selected Antimicrobial Resistance Genes in Poultry Litter from Conventional and Antibiotic-Free Farms - Camilla Smoglica; Muhammad Farooq; Fausto Ruffini; Fulvio Marsilio; Cristina Esmeralda Di Francesco (MDPI AG, 2023)
In this study, a culture-independent approach was applied to compare the microbiome composition and the abundance of the antimicrobial resistance genes (ARGs) aadA2 for aminoglycosides, tet(A), tet(B), tet(K), and tet(M) for tetracyclines, and mcr-1 for colistin in broiler litter samples collected from conventional and antibiotic-free flocks located in Central Italy. A total of 13 flocks and 26 litter samples, collected at the beginning and at the end of each rearing cycle, were submitted to 16s rRNA sequence analysis and quantitative PCR for targeted ARGs. Firmicutes resulted in the dominant phylum in both groups of flocks, and within it, the Clostridia and Bacilli classes showed a similar distribution. Conversely, in antibiotic-free flocks, a higher frequency of Actinobacteria class and Clostridiaceae, Lactobacillaceae, Corynebacteriaceae families were reported, while in the conventional group, routinely treated with antibiotics for therapeutic purposes, the Bacteroidia class and the Enterobacteriaceae and Bacillaceae families were predominant. All investigated samples were found to be positive for at least one ARG, with the mean values of aadA2 and tet(A) the highest in conventional flocks by a significant margin. The results suggest that antibiotic use can influence the frequency of resistance determinants and the microbial community in poultry flocks, even though other environmental factors should also be investigated more deeply in order to identify additional drivers of antimicrobial resistance.